Associations of Placental Oxidative Stress with Exposure to Gestational Air Pollution: Evidence from the UPSIDE Cohort - Emily A. Craig; Yan Lin; Yihui Ge; Xiangtian Wang; Otgondelger Enkhtaivan; Don K. Harrington; Richard K. Miller; Susan K. Murphy; Sally W. Thurston; Philip K. Hopke; Emily S. Barrett; Thomas G. O'Connor; et al. (Environmental Research, 2026)

Pilot study comparing the effects of high dose THC to high dose psilocybin and placebo in the set and setting of a classic psychedelic therapy session - Frederick S. Barrett; David Wolinsky; Zach Daily; Joseph Ciancio; Kristy Arthur; Ryan Vandrey (Psychopharmacology, 2026)
Rationale Delta-9-tetrahydrocannabinol (Δ9-THC) has been reported to evoke psychedelic-like experiences at high doses in some individuals. However, the doses of Δ9-THC that occasion such effects and the phenomenology of these experiences are poorly understood. Objectives This brief report presents preliminary findings from a pilot human laboratory study that directly compared the acute effects of Δ9-THC and psilocybin under set (expectancy) and setting (context) conditions of a typical psychedelic clinical trial. Methods Four healthy adults (ages 31–47, 3 F) received oral administration of placebo, psilocybin (25 mg), and 25 mg Δ9-THC, and two of these participants also received 50 mg Δ9-THC, in a double-blind, placebo-controlled, within-subject crossover study. Δ9-THC was administered as either synthetic Δ9-THC (dronabinol) or a whole-plant cannabis distillate extract (89.9% Δ9-THC). Subjective effects, cardiovascular measures, and safety were monitored throughout each session. Participants were asked after each session what drug they thought they had received. Results 25 mg Δ9-THC in both forms yielded a subjective experience similar to 25 mg psilocybin. Dronabinol was mistaken for a classic hallucinogen by both a psychedelic-naïve and a psychedelic-experienced participant. Conclusions These preliminary data suggest that a 25 mg oral dose of pure, synthetic Δ9-THC can be mistaken for a classic hallucinogen, and that oral Δ9-THC can elicit a psychedelic-like experience under set and setting conditions of a typical psychedelic clinical trial. While limited by sample size, these initial results provide insights into the comparative psychopharmacology of Δ9-THC and psilocybin as well as the potentially substantial impact of set and setting on subjective effects of psychoactive drugs. Trial Registration: This trial was registered at ClinicalTrials.gov (NCT06772753) on January 13, 2025

Exposure to organophosphate esters and trajectories of gestational weight gain: A large prospective cohort study - Belle Martin; David E. Cantonwine; John D. Meeker; Maria Ospina; Antonia M. Calafat; Thomas F. McElrath; Kelly K. Ferguson; Barrett M. Welch (Environmental Research, 2026)

When wood-based thermal mass performs as well as concrete - Remy Fortin; Livia Barrett; Jeff Jeong; Rowe Price; Cory Subasic; David Kennedy; Kiel Moe; Andrew Freear; Salmaan Craig (Energy and Buildings, 2026)

Psilocybin-induced neurocardiogenic syncope: a case report - Mazen A. Atiq; Eli Weisman; Rodrigo B. Guerra; Luis Luna Martinez; David B. Yaden; Frederick S. Barrett; Sandeep Nayak; Ceyda Sayali (Psychopharmacology, 2026)
Background Psilocybin is among the serotonergic psychedelics closest to potential FDA approval, with growing evidence of therapeutic benefit across psychiatric conditions. As clinical trials expand, systematic characterization of adverse events (AEs) remains essential. While transient hypertensive responses are well documented, hypotensive events such as neurocardiogenic syncope (NCS) are rarely reported. Case presentation We describe a healthy 35‑year‑old male enrolled in an open‑label study investigating psilocybin‑evoked changes in brain function during transcranial magnetic stimulation and electroencephalography (TMS‑EEG). Approximately 60 minutes after receiving 25 mg oral psilocybin, and shortly after initiation of an eye‑open resting‑state EEG, he experienced prodromal lightheadedness followed by a brief loss of consciousness and postural tone. Immediate blood pressure was 93/51 mmHg with tachycardia and diaphoresis. Supportive measures, including leg elevation and oral hydration, led to rapid stabilization, and no further cardiovascular abnormalities occurred. The participant reported an emotionally intense experience, and contextual factors - including upright seated posture, restrictive EEG equipment, and anticipatory anxiety surrounding TMS - may have contributed to heightened autonomic arousal and susceptibility to NCS. Conclusions This case highlights a rare hypotensive AE during psilocybin administration and underscores the importance of vigilant cardiovascular monitoring, particularly during procedures that may amplify emotional arousal. Given that fewer than one‑quarter of contemporary psychedelic trials report systematic AE assessment, transparent documentation of both hypertensive and hypotensive events is critical for defining psilocybin’s safety profile as clinical applications expand. Parent trial registration Open Label Psilocybin Brain Stimulation and Imaging Pilot Study; ClinicalTrials.gov: NCT06835699. Date registered: 02/13/2025. The parent‑study consent form explicitly permits publication of de‑identified participant data, and separate institutional approval for this case report was obtained (IRB00543773).

Plasma pTau181 is associated with subjective cognitive concerns but not objective cognitive decline or structural brain integrity measures in midlife - Ashleigh Barrett-Young; Erin E. Cawston; Brigid Ryan; Wickliffe C. Abraham; Antony Ambler; Tim Anderson; Kirsten Cheyne; Elizabeth Goodin; Sean Hogan; Renate M. Houts; David Ireland; Annchen R. Knodt; et al. (GeroScience, 2026)
Although plasma pTau181 has been shown to accurately discriminate patients with Alzheimer’s disease from healthy older adults, there are few studies of plasma biomarkers among middle-aged populations. Given the potential utility of plasma AD biomarkers such as pTau181 in screening for disease risk, examining pTau181 in a middle-aged cohort without AD is important for future implementation. The objectives of this study were to characterise plasma pTau181 in a middle-aged birth cohort aged 45 years and to investigate associations with early indicators of dementia risk. Participants were members of the Dunedin Multidisciplinary Health and Development Study, a longitudinal study of 1037 people born in New Zealand in 1972–1973. Plasma pTau181, self-reported cognitive concerns, MRI-based brain structure, and DunedinPACE (an epigenetic biomarker of biological ageing) were measured at age 45; cognition was measured in childhood and age 45. Plasma pTau181 concentrations at age 45 ( n = 854, 49% female) were associated with self-reported cognitive concerns (β = 0.09, p = .008); however, no significant associations were observed with objective cognitive decline, worse structural brain integrity, or biological ageing. Higher plasma pTau181 was associated with self-reported cognitive concerns at age 45, but not objective AD-related measures. The association of plasma pTau181 and self-reported cognitive concerns in this cohort suggests that AD pathology may begin to accumulate by age 45 and may be associated with subtle changes in cognition that are not at objectively measurable levels. Graphical Abstract

Ultra-Violet Induced Biochemical Changes in an Invasive Weed and their Implications for Plant-Biocontrol Agent Interactions - D. Paul Barrett; Arvind K. Subbaraj; Jason J. Wargent; Maria A. Minor; Paul Peterson; David J. Lun; Andrea Clavijo McCormick (Journal of Chemical Ecology, 2026)
Introducing insect biocontrol agents sourced from a plant’s native range is an effective, sustainable management strategy for invasive plants. However, not all biocontrol programmes achieve the desired outcome because control agents either fail to establish or are ineffective. Heather beetle Lochmaea suturalis (Coleoptera: Chrysomelidae), introduced from the United Kingdom (UK) to New Zealand (NZ) to control the invasive shrub Calluna vulgaris (heather), was difficult to establish and achieved poor population growth rates and expansion relative to its conspecifics in its native UK range. Poor performance in biocontrol is often attributed to various abiotic or biotic factors but seldom considers alterations to a target plants biochemical phenotype. A recent study revealed, heather has a significantly different biochemical profile in NZ compared with the UK, between which there is considerable difference in ultra-violet (UV) radiation. UV is known to drive plant biochemical change, including defensive secondary metabolites and we hypothesized that this factor could enhance heathers’ defensive capability leading to poor biocontrol agent performance. Testing this hypothesis involved exposing heather plants to 20% and 95% UV attenuating screens and using metabolomics to measure plant secondary metabolite responses. Our results demonstrate significant alterations to many compounds derived from the shikimate-phenylpropanoid pathway. However, a bioassay revealed no impact on prepupal weight or larval survival of the biocontrol agent L. suturalis . We discuss and explore possible reasons for this outcome, the magnitude and impact of UV-induced biochemical changes on plant-insect interactions and the potential of metabolomics to support weed biocontrol.

Using herd frailty estimates from survival models in a mortality-based syndromic surveillance system - Jaden M. Carlson; T. Brendan Murphy; Luke O’Grady; Jonas Brock; Maria P. Guelbenzu-Gonzalo; David A. Graham; Guy McGrath; Jamie A. Tratalos; Rafael de Andrade Moral; Niamh Mimnagh; Niamh L. Field; John F. Mee; et al. (Preventive Veterinary Medicine, 2026)

Low foliar nitrogen and elevated defensive metabolites in the invasive weed Calluna vulgaris (heather) may impair biocontrol agent performance - D. Paul Barrett; Maria A. Minor; Paul Peterson; Simon V. Fowler; Arvind K. Subbaraj; David J. Lun; Andrea Clavijo McCormick (Biological Invasions, 2026)
Introducing insect biocontrol agents to manage invasive plants is an effective and sustainable management option. However, biocontrol agents sometimes fail to establish or are ineffective in the new range. Heather beetle Lochmaea suturalis, (Thomson, 1866) (Coleoptera: Chrysomelidae) sourced from the United Kingdom (UK), was introduced into New Zealand’s North Island Central Plateau (CP) to control invasive Calluna vulgaris (L.) Hull (heather). The beetle was difficult to establish and the few populations that did, achieved poor population growth rates and expansion in contrast to the rapid rates associated with its conspecifics in the UK. We hypothesize that low soil nutrients such as nitrogen and phosphorous (N and P) on the CP may be linked to changes in C. vulgaris’ primary nutritional and secondary defensive metabolites, leading to poor beetle performance. Testing this hypothesis involved application of N and P to soil in C. vulgaris field plots, measurement of foliar N and Carbon (C), plus using non-targeted metabolomics, exploring differences in the primary and secondary metabolites between treatments. Raising soil nutrients amplified several primary metabolites including N-based amino acids and concomitantly reduced the majority of phenylpropanoids, a secondary metabolite group containing many defensive compounds. This work seeks to better understand, how abiotic conditions in a new environment, influence invasive plant metabolism, potentially altering the efficiency of foliage assimilation which may impair biocontrol agent establishment and effectiveness. Such understanding may be applied to mitigate potential foliar deficiencies at release sites and contribute to improving success rates of biocontrol as a management strategy for invasive plants.

Prenatal air pollution exposure and placental vasculature development among participants of the UPSIDE cohort study - Shivram Kumar; Carolyn M. Salafia; Ruchit Shah; Theresa Girardi; Richard K. Miller; Sally W. Thurston; Philip K. Hopke; David Skrill; Jessica Brunner; Donald Harrington; Yihui Ge; Yan Lin; et al. (Environmental Research, 2025)

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

Forest restoration treatments increase native plant diversity but open the door to invasion in the Colorado Front Range - Adam L. Mahood; Camille S. Stevens-Rumann; Allison E. Rhea; Scott M. Ritter; Kevin Barrett; Paula J. Fornwalt; David M. Barnard (Forest Ecology and Management, 2025)

From cow sense to data sense: hybrid epistemologies on US dairy farms - Jaime Barrett; David Lansing (Journal of Rural Studies, 2025)

Wildlife response to land-use change forces encounters between zoonotic disease hosts and farms in agricultural landscapes - Kilian J. Murphy; Andrew W. Byrne; Nicola Marples; Maria J.H. O’Hagan; David J. Kelly; David Quinn; Phillip Breslin; Virginia Morera-Pujol; Renée M. Khouri; Damien Barrett; Guy McGrath; Simone Ciuti (Agriculture, Ecosystems & Environment, 2025)

Targeting carbon reduction in UK households: A new segmentation model using financial transaction data - Jasmine Wells; Anna Trendl; Anne Owen; John Barrett; Norbert Jobst; David Leake (Journal of Industrial Ecology, 2025)
Designing effective and targeted policies to reduce household emissions needs to consider variability in household consumption patterns, preferences, and financial capacities. This paper introduces a new segmentation model of household carbon footprints that uses financial transaction data from over 700,000 customers of a major high‐street bank. Our approach considers socioeconomic, consumer‐preference, and spatial factors to identify 10 distinct household typologies. We focus on targeted retrofit as a practical application, identifying three high‐impact household types with the capacity to invest— “Suburban Home Improvers,” “Car and Tech Enthusiasts,” and “Affluent Families”— and suggest targeted policy and communication opportunities. Our segmentation supports a new data‐driven policy design that considers both the technical potential and diverse behavioral factors affecting decarbonization decisions.

Beyond borders: A systematic review and meta-analysis of human-specific faecal markers across geographical settings - Leah R. Barrett; Paris Beasy; Yussi M. Palacios Delgado; John D. Boyce; Karin Leder; David T. McCarthy; Rebekah Henry (Critical Reviews in Environmental Science and Technology, 2025)

Evaluating the influence of snow and ice conditions on under‐ice light regimes, dissolved oxygen, and primary production in shallow lakes using controlled manipulative systems - David C. Barrett; Frederick J. Wrona (Limnology and Oceanography, 2025)
Shifts in hydroclimatic regimes associated with global climate change are affecting the timing and duration of winter ice‐cover in temperate and high‐latitude lakes. Less is known on how associated changes in ice quality potentially affect under‐ice ecological processes and related biogeochemistry, particularly in shallow lake systems. This experimental study examined how differing surface ice‐cover types (slushed white ice, unmanipulated ice formation [black], snow‐on‐ice) affected under‐ice light and oxygen regimes and associated chlorophyll a concentrations, and water quality parameters using a combination of aboveground mesocosms and natural ponds over two consecutive winter seasons. In both systems, light transmission under white ice did not differ significantly from black but was significantly greater than snow‐on‐ice. Measures of light extinction coefficients taken at the ice‐water interface in the experimental ponds increased for black, white, and snow‐on‐ice, respectively, with all values being above thresholds for autotrophic activity. Under‐ice dissolved oxygen levels in all mesocosm ice treatments increased continually over time with increasing day length, peaking prior to ice off. Accumulated DO levels were aligned with observed chlorophyll a concentrations, with peaks early after ice onset, and decreases as winter progressed though patterns differed between years. No significant differences were observed in mean chlorophyll a levels in snow‐removed treatment ponds, regardless of whether white or black ice was present while the snow‐on‐ice ponds displayed consistently lower levels. This study highlights the complexities and importance of using manipulative experimental approaches to advance our understanding of how alterations in surface ice‐cover quality affect under‐ice hydro‐ecological processes.

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Prenatal exposure to phthalates and phthalate replacements in relation to chorionic plate surface vasculature at delivery - Emily S. Barrett; David Skrill; Elaine Zhou; Sally W. Thurston; Theresa Girardi; Jessica Brunner; Hai-Wei Liang; Richard K. Miller; Carolyn M. Salafia; Thomas G. O'Connor; Jennifer J. Adibi (Science of The Total Environment, 2025)

Sea Country Indigenous Protected Areas: Indigenous leadership in the protection of Australia’s marine environments - Janella Isaac; Rowena Mouda; David Barrett; Jackie Gould; Dermot Smyth; Tanya Vernes (Marine Policy, 2024)

Exposure to organophosphate ester flame retardants and plasticizers and associations with preeclampsia and blood pressure in pregnancy - Amir J. Lueth; Paige A. Bommarito; Danielle R. Stevens; Barrett M. Welch; David E. Cantonwine; Maria Ospina; Antonia M. Calafat; John D. Meeker; Thomas F. McElrath; Kelly K. Ferguson (Environmental Research, 2024)

Coordinated microanalysis of volatiles in apatite and silicate minerals in ancient lunar basalts - Thomas J. Barrett; Katharine L. Robinson; Kazuhide Nagashima; Barry J. Shaulis; Gary R. Huss; David A. Kring (Chemical Geology, 2024)

Evaluating the effectiveness & costs of strategies post-eradication to monitor for freedom from BVDV infection in Ireland - Jonas Brock; Maria Guelbenzu-Gonzalo; Martin Lange; Jamie A. Tratalos; Damien Barrett; Liz Lane; Simon J. More; David A. Graham; Hans-Hermann Thulke (Agricultural Systems, 2024)

The Once and Future Fish: Assessing a Millennium of Atlantic Herring Exploitation Through Mixed‐Stock Analysis and Ancient DNA - Lane M. Atmore; Inge van der Jagt; Aurélie Boilard; Simone Häberle; Rachel Blevis; Katrien Dierickx; Liz M. Quinlan; David C. Orton; Anne Karin Hufthammer; James H. Barrett; Bastiaan Star (Global Change Biology, 2024)
Small pelagic fish support profitable fisheries and are important for food security around the world. Yet, their sustainable management can be hindered by the indiscriminate impacts of simultaneous exploitation of fish from multiple distinct biological populations over extended periods of time. The quantification of such impacts is greatly facilitated by recently developed molecular tools—including diagnostic single nucleotide polymorphism (SNP) panels for mixed‐stock analysis (MSA)—that can accurately detect the population identity of individual fish. However, the biological relevance of such tools over longer periods of time remains unknown. Here, we demonstrate that diagnostic SNP panels designed for contemporary MSA in Atlantic herring have a millennium‐long biological relevance and applicability. We assign the population identity of ancient Atlantic herring specimens—obtained through famously profitable historic fisheries—up to 1300 years old from eight archaeological sites across Europe. Analyzing contemporary and ancient whole‐genome data, we obtain evidence for the long‐term mixed‐stock exploitation of Atlantic herring. Despite such mixed‐stock exploitation, we exclusively identify autumn‐spawning herring amongst these archaeological remains, indicative of a specific biological availability or cultural preference for certain herring ecotypes in the past. Moreover, our results show that herring demographic patterns were relatively stable until the dramatic disruptions and stock collapses during the 20th century. We find small but significant reductions in genetic diversity over time, indicating long‐term evolutionary consequences from 20th‐century stock declines. The long‐term applicability of diagnostic SNP panels underscores their biological relevance and cost‐effective application for the genetic monitoring of herring stocks and highlights the utility of ancient DNA to obtain insights in herring ecology and population dynamics.

Active wave energy extraction by hydrofoil vessels through deep reinforcement learning-based flight control - John Martin Kleven Godø; Sverre Steen; David Barrett; Michael S. Triantafyllou (Ocean Engineering, 2024)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

Collaborative anthracology and cultural understandings of wood charcoal in Marra Country (northern Australia) - Matthew Walsh; Emilie Dotte-Sarout; Liam M. Brady; John Bradley; Jeremy Ash; Daryl Wesley; Shaun Evans; David Barrett (Archaeological and Anthropological Sciences, 2024)
This paper presents results from the first collaborative anthracological (archaeological wood charcoal analysis) study in northern Australia’s southwest Gulf of Carpentaria region. The analysis focused on charcoal from a Late Holocene combustion feature and surrounding dispersed charcoal on a buried floor surface. The results suggest that the combustion feature likely functioned as a ground oven associated with a potential specific function, with the majority of fuel wood coming from wakuwaku/marnunggurrun ( Callitris columellaris or White Cypress Pine) and Myrtaceae species. These species are found in low woodlands associated with hilly and freshwater springs settings, and their abundance and dispersal are influenced by fire regimes (e.g., Aboriginal fire regimes). Information provided by members of the Marra Aboriginal community about our findings focused on the social and cultural significance of wakuwaku/marnunggurrun , with particular emphasis around its role in past and present wood collection strategies (fire-making and transport, high value timber etc.). By exploring how anthracology and cultural knowledge intersect to generate new understandings about the relational qualities of wood (charcoal), we aim to highlight how collaborative archaeobotany can help reorient research questions in the discipline, providing an opportunity to make such specialised analyses meaningful to communities.

Counter‐gradient variation in gene expression between fish populations facilitates colonization of low‐dissolved oxygen environments - Janay A. Fox; David A. G. A. Hunt; Andrew P. Hendry; Lauren J. Chapman; Rowan D. H. Barrett (Molecular Ecology, 2024)
The role of phenotypic plasticity during colonization remains unclear due to the shifting importance of plasticity across timescales. In the early stages of colonization, plasticity can facilitate persistence in a novel environment; but over evolutionary time, processes such as genetic assimilation may reduce variation in plastic traits such that species with a longer evolutionary history in an environment can show lower levels of plasticity than recent invaders. Therefore, comparing species in the early stages of colonization to long‐established species provides a powerful approach for uncovering the role of phenotypic plasticity during different stages of colonization. We compared gene expression between low‐dissolved oxygen (DO) and high‐DO populations of two cyprinid fish: Enteromius apleurogramma , a species that has undergone a recent range expansion, and E. neumayeri , a long‐established native species in the same region. We sampled tissue either immediately after capture from the field or after a 2‐week acclimation under high‐DO conditions, allowing us to test for both evolved and plastic differences in low‐DO vs high‐DO populations of each species. We found that most genes showing candidate‐evolved differences in gene expression did not overlap with those showing plastic differences in gene expression. However, in the genes that did overlap, there was counter‐gradient variation such that plastic and evolved gene expression responses were in opposite directions in both species. Additionally, E. apleurogramma had higher levels of plasticity and evolved divergence in gene expression between field populations. We suggest that the higher level of plasticity and counter‐gradient variation may have allowed rapid genetic adaptation in E. apleurogramma and facilitated colonization. This study shows how counter‐gradient variation may impact the colonization of divergent oxygen environments.

Muscle Morphology Does Not Solely Determine Knee Flexion Weakness After Anterior Cruciate Ligament Reconstruction with a Semitendinosus Tendon Graft: A Combined Experimental and Computational Modeling Study - Adam Kositsky; Lauri Stenroth; Rod S. Barrett; Rami K. Korhonen; Christopher J. Vertullo; Laura E. Diamond; David J. Saxby (Annals of Biomedical Engineering, 2024)
The distal semitendinosus tendon is commonly harvested for anterior cruciate ligament reconstruction, inducing substantial morbidity at the knee. The aim of this study was to probe how morphological changes of the semitendinosus muscle after harvest of its distal tendon for anterior cruciate ligament reconstruction affects knee flexion strength and whether the knee flexor synergists can compensate for the knee flexion weakness. Ten participants 8–18 months after anterior cruciate ligament reconstruction with an ipsilateral distal semitendinosus tendon autograft performed isometric knee flexion strength testing (15°, 45°, 60°, and 90°; 0° = knee extension) positioned prone on an isokinetic dynamometer. Morphological parameters extracted from magnetic resonance images were used to inform a musculoskeletal model. Knee flexion moments estimated by the model were then compared with those measured experimentally at each knee angle position. A statistically significant between-leg difference in experimentally-measured maximal isometric strength was found at 60° and 90°, but not 15° or 45°, of knee flexion. The musculoskeletal model matched the between-leg differences observed in experimental knee flexion moments at 15° and 45° but did not well estimate between-leg differences with a more flexed knee, particularly at 90°. Further, the knee flexor synergists could not physiologically compensate for weakness in deep knee flexion. These results suggest additional factors other than knee flexor muscle morphology play a role in knee flexion weakness following anterior cruciate ligament reconstruction with a distal semitendinosus tendon graft and thus more work at neural and microscopic levels is required for informing treatment and rehabilitation in this demographic.

Non-native plant invasion after fire in western USA varies by functional type and with climate - Janet S. Prevéy; Catherine S. Jarnevich; Ian S. Pearse; Seth M. Munson; Jens T. Stevens; Kevin J. Barrett; Jonathan D. Coop; Michelle A. Day; David Firmage; Paula J. Fornwalt; Katharine M. Haynes; James D. Johnston; et al. (Biological Invasions, 2024)

On the rebound: removal programs yield local-scale benefits but do not sustainably suppress populations of invasive European green crabs (Carcinus maenas) - Paula Tummon Flynn; Luke A. Poirier; Gabrielle Beaulieu; Timothy J. Barrett; David K. Cairns; Pedro A. Quijón (Biological Invasions, 2024)

Deciphering the origin(s) of H and Cl in Apollo 15 quartz monzodiorites: Evidence for multiple processes and reservoirs - Thomas J. Barrett; Katharine L. Robinson; Jessica J. Barnes; G. Jeffrey Taylor; Kazuhide Nagashima; Gary R. Huss; Ian A. Franchi; Mahesh Anand; David A. Kring (Geochimica et Cosmochimica Acta, 2023)

Exploring palaeoecology in the Northern Territory: the Walanjiwurru rockshelter, vegetation dynamics and shifting social landscapes in Marra Country - Cassandra Rowe; Jeremy Ash; Liam M. Brady; Daryl Wesley; Shaun Evans; David Barrett (Vegetation History and Archaeobotany, 2023)
This paper presents a palynological analysis of sediments from Walanjiwurru 1, a rockshelter located in the Country of the Marra Aboriginal people at Limmen National Park in the Northern Territory (Australia). Analysis seeks to test rockshelter sediments as a framework for research in an environmentally difficult location, and to explore how the palaeoecological record may capture the diversity of people-nature relationships over time in the Northern Territory. The Walanjiwurru 1 pollen record provides an approximate 500-year insight into the rockshelter’s surrounding landscape. Two plant communities demonstrate local presence across this time frame—foremost a drier eucalypt woodland, and a wetter fringing Melaleuca dominated habitat, each with an integrated series of monsoonal forest taxa. With only subtle shifts in vegetation, the Marra’s consistent maintenance of relations with their landscape is observable, and this is discussed in relation to the Walanjiwurru 1’s archaeology and regional European settler colonialism. Charcoal recovery from Walanjiwurru 1 is derived from in situ campfires, making it difficult to conclude on the response of plant types and vegetation communities to long-term landscape burning. Future palaeoecological research off-site from the rockshelter has therefore been recommended.

Delivering on sustainable development goals in wastewater reuse for agriculture: Initial prioritization of emerging pollutants in the Tula Valley, Mexico - Andrea-Lorena Garduño-Jiménez; Juan-Carlos Durán-Álvarez; Catharine A. Ortori; Salah Abdelrazig; David A. Barrett; Rachel L. Gomes (Water Research, 2023)

Maternal exposure to phthalates and total gestational weight gain in the LIFECODES birth cohort - Theresa M. Boyer; Paige A. Bommarito; Barrett M. Welch; John D. Meeker; Tamarra James-Todd; David E. Cantonwine; Thomas F. McElrath; Kelly K. Ferguson (Reproductive Toxicology, 2023)

Prioritizing taxa for genetic reference database development to advance inland water conservation - Marie-Eve Monchamp; Zofia E. Taranu; Rebecca E. Garner; Tessa Rehill; Olivier Morissette; Lars L. Iversen; Vincent Fugère; Joanne E. Littlefair; Naíla Barbosa da Costa; Jessica E. Desforges; Joe R. Sánchez Schacht; Alison M. Derry; et al. (Biological Conservation, 2023)

Environmental and geographical factors structure cauliflower coral's algal symbioses across the Indo‐Pacific - Victoria M. Glynn; Steven V. Vollmer; David I. Kline; Rowan D. H. Barrett (Journal of Biogeography, 2023)
Aim The symbioses between corals and endosymbiotic dinoflagellates have been described as a flexible relationship whose dynamics could serve as a source of resilience for coral reef ecosystems. However, the factors that drive the establishment and maintenance of this co‐evolutionary relationship remain unclear. We examined the environmental and geographical factors structuring dinoflagellate communities in a wide‐ranging Indo‐Pacific coral to begin to address this gap. Location Djibouti, Oman, Taiwan and French Polynesia. Taxon Cauliflower corals ( Pocillopora spp.), dinoflagellates (family Symbiodiniaceae). Methods We analysed publicly available amplicon sequence data from the nuclear ribosomal DNA internal transcribed spacer 2, originating from Pocillopora spp. We also compiled environmental data such as sea surface temperature (SST) and time since the last local mass bleaching event. We ran generalized least squares models, PERMANOVAs and indicator species analyses, to understand how thermal regimes and geographical distances impacted Pocillopora spp.'s Symbiodiniaceae community composition. Results Sea surface temperature was the most important factor driving Symbiodiniaceae community differences, with the largest effect size of the statistically significant factors. When focusing on individual Symbiodiniaceae genera, SST was likewise the most important factor. Our indicator species analyses revealed that specimens that had recently bleached were characterized by roughly equal proportions of Cladocopium spp. and Durusdinium spp., while specimens that had not recently bleached had a similar proportion of Durusdinium spp. as those that had recently bleached, but also showed a reduction in Cladocopium spp., with this deficiency made up by the presence of Symbiodinium spp. Main Conclusions We provide further support for the hypothesis that coral's Symbiodiniaceae communities could facilitate host resilience to thermal stress. Our work is in direct conversation with a larger body of biogeography literature that highlights how local environmental regimes can impact contemporary population structure, even in marine taxa with widespread distributions.

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Patient–Specific Immersed Finite Element–Difference Model of Transcatheter Aortic Valve Replacement - Jordan A. Brown; Jae H. Lee; Margaret Anne Smith; David R. Wells; Aaron Barrett; Charles Puelz; John P. Vavalle; Boyce E. Griffith (Annals of Biomedical Engineering, 2023)
Transcatheter aortic valve replacement (TAVR) first received FDA approval for high-risk surgical patients in 2011 and has been approved for low-risk surgical patients since 2019. It is now the most common type of aortic valve replacement, and its use continues to accelerate. Computer modeling and simulation (CM&S) is a tool to aid in TAVR device design, regulatory approval, and indication in patient-specific care. This study introduces a computational fluid-structure interaction (FSI) model of TAVR with Medtronic’s CoreValve Evolut R device using the immersed finite element-difference (IFED) method. We perform dynamic simulations of crimping and deployment of the Evolut R, as well as device behavior across the cardiac cycle in a patient-specific aortic root anatomy reconstructed from computed tomography (CT) image data. These IFED simulations, which incorporate biomechanics models fit to experimental tensile test data, automatically capture the contact within the device and between the self-expanding stent and native anatomy. Further, we apply realistic driving and loading conditions based on clinical measurements of human ventricular and aortic pressures and flow rates to demonstrate that our Evolut R model supports a physiological diastolic pressure load and provides informative clinical performance predictions.

The PMEL Earth-Ocean Interactions Program: Beyond Vents - David Butterfield; Sharon Walker; Tamara Baumberger; Jeff Beeson; Joseph Resing; Susan Merle; Anson Antriasian; Kevin Roe; Guang-Sin Lu; Pamela Barrett; William Chadwick (Oceanography, 2023)
As previously summarized by Hammond et al. (2015), from 1983 to 2013, the NOAA Vents program conducted systematic and multidisciplinary exploration, discovery, and research related to hydrothermal vents, submarine volcanic eruptions, and associated ocean physical, chemical, and biological processes. In 2014, Vents divided into two programs, Earth-Ocean Interactions (EOI) and Acoustics, and considered a broader range of questions about how seafloor and subseafloor processes contribute to ocean health, biogeochemical cycles, ecosystem diversity, and climate change. Here, we highlight major accomplishments since 2014, including deep-sea technologies that EOI, Vents, and Pacific Marine Environmental Laboratory (PMEL) Engineering have developed to advance marine science. EOI research is driven by a need for better observational data on issues of global importance, including the role of continental margin seeps in the global methane/carbon cycle, benthic ecology, and fisheries habitat; the role of hydrothermal systems in global biogeochemical cycles, including carbon dioxide removal; the potential impact of deep-sea mining of metal sulfides on ecosystem services provided by hydrothermal vents; and how hydrothermal iron functions as an essential nutrient. NOAA Ocean Exploration, the Schmidt Ocean Institute, the Ocean Exploration Trust, and the National Science Foundation have supported and collaborated in this work. Global exploration of the deep sea with the purpose of understanding global ocean processes remains a cornerstone of EOI science.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

The contribution of macroalgae‐associated fishes to small‐scale tropical reef fisheries - Shaun K. Wilson; Christopher J. Fulton; Nicholas A.J. Graham; Rene A. Abesamis; Charlotte Berkström; Darren J. Coker; Martial Depczynski; Richard D. Evans; Rebecca Fisher; Jordan Goetze; Andrew Hoey; Thomas H. Holmes; et al. (Fish and Fisheries, 2022)
Macroalgae‐dominated reefs are a prominent habitat in tropical seascapes that support a diversity of fishes, including fishery target species. To what extent, then, do macroalgal habitats contribute to small‐scale tropical reef fisheries? To address this question we: (1) Quantified the macroalgae‐associated fish component in catches from 133 small‐scale fisheries, (2) Compared life‐history traits relevant to fishing (e.g. growth, longevity) in macroalgal and coral‐associated fishes, (3) Examined how macroalgae‐associated species can influence catch diversity, trophic level and vulnerability and (4) Explored how tropical fisheries change with the expansion of macroalgal habitats using a case study of fishery‐independent data for Seychelles. Fish that utilised macroalgal habitats comprise 24% of the catch, but very few fished species relied entirely on macroalgal or coral habitats post‐settlement. Macroalgal and coral‐associated fishes had similar life‐history traits, although vulnerability to fishing declined with increasing contribution of macroalgae association to the catch, whilst mean trophic level and diversity peaked when macroalgal‐associated fish accounted for 20%–30% of catches. The Seychelles case study revealed similar total fish biomass on macroalgal and coral reefs, although the biomass of primary target species increased as macroalgae cover expanded. Our findings reinforce that multiple habitat types are needed to support tropical fishery stability and sustainability. Whilst coral habitats have been the focus of tropical fisheries management, we show the potential for macroalgae‐associated fish to support catch size and diversity in ways that reduce vulnerability to overfishing. This is pertinent to seascapes where repeated disturbances are facilitating the replacement of coral reef with macroalgal habitats.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Understanding the role of topography on the diurnal cycle of precipitation in the Maritime Continent during MJO propagation - Haochen Tan; Pallav Ray; Bradford Barrett; Jimy Dudhia; Mitchell Moncrieff; Lei Zhang; David Zermeno-Diaz (Climate Dynamics, 2022)

Correction to: Imaging tools for assessment of myocardial fibrosis in humans: the need for greater detail - Summer Hassan; Carolyn J Barrett; David J Crossman (Biophysical Reviews, 2022)

Effects of human footprint and biophysical factors on the body‐size structure of fished marine species - Nestor E. Bosch; Jacquomo Monk; Jordan Goetze; Shaun Wilson; Russell C. Babcock; Neville Barrett; Jock Clough; Leanne M. Currey‐Randall; David V. Fairclough; Rebecca Fisher; Brooke A. Gibbons; David Harasti; et al. (Conservation Biology, 2022)
Marine fisheries in coastal ecosystems in many areas of the world have historically removed large‐bodied individuals, potentially impairing ecosystem functioning and the long‐term sustainability of fish populations. Reporting on size‐based indicators that link to food‐web structure can contribute to ecosystem‐based management, but the application of these indicators over large (cross‐ecosystem) geographical scales has been limited to either fisheries‐dependent catch data or diver‐based methods restricted to shallow waters (

Quota allocation for stocks that span multiple management zones: analysis with a vector autoregressive spatiotemporal model - Charles F. Adams; Elizabeth N. Brooks; Christopher M. Legault; Melanie A. Barrett; David F. Chevrier (Fisheries Management and Ecology, 2021)
Allocating quotas among stakeholders requires an agreed‐upon formula. If the stock unit spans multiple management jurisdictions, the formula may require updated biomass estimates of the stock's spatial distribution with respect to those jurisdictions. Data for calculating stock biomass often come from fishery‐independent surveys. While stratified random sampling is a common design, strata boundaries may not always align with state or national jurisdictions, requiring post hoc stratification and imputation to calculate area‐specific biomass. The vector autoregressive spatiotemporal (VAST) model was explored as a tool for calculating fish biomass within subareas of a defined stock unit for three different stocks jointly managed by the United States and Canada on Georges Bank in the Northwest Atlantic Ocean. VAST estimated proportions of stock biomass in each nation's waters were compared with an existing allocation algorithm that utilises a loess smooth through the average design‐based swept area biomass from three fishery‐independent surveys. The ability of VAST to impute biomass when no tows occur in a subarea of a survey stratum was demonstrated, as well as the relatively smoother biomass trend compared with design‐based estimates, which may be desirable if the intent is to avoid large inter‐annual swings in allocated quota.

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Rebecca Fisher; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish Malcolm; Leanne M. Currey‐Randall; Daniel Ierodiaconou; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia‐wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta‐analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance‐based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no‐take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.

An unexpected backyard hunter: breeding Barred Owls exhibit plasticity in habitat selection along a development gradient - Marion A. Clément; Kyle Barrett; Robert F. Baldwin; Catherine M. Bodinof Jachowski; Addie Carter; David Brinker (Urban Ecosystems, 2021)

A review of American lobster (Homarus americanus) records around the British Isles: 2012 to 2018 - Christopher John Barrett; Alastair Cook; David Stone; Chris Evans; Debbie Murphy; Paul Johnson; Marc Thain; Gabrielle Wyn; Mark Grey; Hugh Edwards; Declan Quigley; Paul Douglas Stebbing (Hydrobiologia, 2020)

Imaging tools for assessment of myocardial fibrosis in humans: the need for greater detail - Summer Hassan; Carolyn J Barrett; David J Crossman (Biophysical Reviews, 2020)

Macroalgal meadow habitats support fish and fisheries in diverse tropical seascapes - Christopher J. Fulton; Charlotte Berkström; Shaun K. Wilson; Rene A. Abesamis; Michael Bradley; Carolina Åkerlund; Luke T. Barrett; Abner A. Bucol; Dinorah H. Chacin; Karen M. Chong‐Seng; Darren J. Coker; Martial Depczynski; et al. (Fish and Fisheries, 2020)
Canopy‐forming macroalgae can construct extensive meadow habitats in tropical seascapes occupied by fishes that span a diversity of taxa, life‐history stages and ecological roles. Our synthesis assessed whether these tropical macroalgal habitats have unique fish assemblages, provide fish nurseries and support local fisheries. We also applied a meta‐analysis of independent surveys across 23 tropical reef locations in 11 countries to examine how macroalgal canopy condition is related to the abundance of macroalgal‐associated fishes. Over 627 fish species were documented in tropical macroalgal meadows, with 218 of these taxa exhibiting higher local abundance within this habitat (cf. nearby coral reef) during at least one life‐history stage. Major overlap (40%–43%) in local fish species richness among macroalgal and seagrass or coral reef habitats suggest macroalgal meadows may provide an important habitat refuge. Moreover, the prominence of juvenile fishes suggests macroalgal meadows facilitate the triphasic life cycle of many fishes occupying diverse tropical seascapes. Correlations between macroalgal canopy structure and juvenile abundance suggests macroalgal habitat condition can influence levels of replenishment in tropical fish populations, including the majority of macroalgal‐associated fishes that are targeted by commercial, subsistence or recreational fisheries. While many macroalgal‐associated fishery species are of minor commercial value, their local importance for food and livelihood security can be substantial (e.g. up to 60% of landings in Kenyan reef fisheries). Given that macroalgal canopy condition can vary substantially with sea temperature, there is a high likelihood that climate change will impact macroalgal‐associated fish and fisheries.

Relationships among white-tailed deer density, harvest, and landscape metrics in TN, USA - Heidi L. Adams; Robert E. Kissell; Daryl Ratajczak; Edward L. Warr; Roger D. Applegate; Lynn Barrett; Tabitha Lavacot; David Graves (European Journal of Wildlife Research, 2020)
Landscape and harvest indices are frequently used to represent white-tailed deer ( Odocoileus virginianus ) density. However, the relationship between deer density and specific landscape indices is unclear. Harvest is another metric often used to estimate deer density. Our objective was to model the relationship among deer density, landscape metrics, and harvest density of deer in TN, USA. We estimated deer density across 11 regions in 2011 using distance sampling techniques. We developed 18 a priori models to assess relationships among deer density, harvest density, and landscape metrics. Estimates of deer density ranged from 1.85 to 19.99 deer/km 2 . Deer density was best predicted by harvest density and harvest density + percent woody area. However, harvest density was the only important variable in predicting deer density (Σω i = 0.700). Results of this study emphasize the significance of harvest density in deer management. While the importance of harvest as a management tool for deer is likely to increase as landscapes are fragmented and urbanized, specific management guidelines should be based upon deer densities and landscape metrics when they are important.

Evaluating the power of photogrammetry for monitoring killer whale body condition - Holly Fearnbach; John W. Durban; Lance G. Barrett‐Lennard; David K. Ellifrit; Kenneth C. Balcomb (Marine Mammal Science, 2020)

Artificial intelligence supported patient self-care in chronic heart failure: a paradigm shift from reactive to predictive, preventive and personalised care - Matthew Barrett; Josiane Boyne; Julia Brandts; Hans-Peter Brunner-La Rocca; Lieven De Maesschalck; Kurt De Wit; Lana Dixon; Casper Eurlings; Donna Fitzsimons; Olga Golubnitschaja; Arjan Hageman; Frank Heemskerk; et al. (EPMA Journal, 2019)
Heart failure (HF) is one of the most complex chronic disorders with high prevalence, mainly due to the ageing population and better treatment of underlying diseases. Prevalence will continue to rise and is estimated to reach 3% of the population in Western countries by 2025. It is the most important cause of hospitalisation in subjects aged 65 years or more, resulting in high costs and major social impact. The current “one-size-fits-all” approach in the treatment of HF does not result in best outcome for all patients. These facts are an imminent threat to good quality management of patients with HF. An unorthodox approach from a new vision on care is required. We propose a novel predictive, preventive and personalised medicine approach where patients are truly leading their management, supported by an easily accessible online application that takes advantage of artificial intelligence. This strategy paper describes the needs in HF care, the needed paradigm shift and the elements that are required to achieve this shift. Through the inspiring collaboration of clinical and high-tech partners from North-West Europe combining state of the art HF care, artificial intelligence, serious gaming and patient coaching, a virtual doctor is being created. The results are expected to advance and personalise self-care, where standard care tasks are performed by the patients themselves, in principle without involvement of healthcare professionals, the latter being able to focus on complex conditions. This new vision on care will significantly reduce costs per patient while improving outcomes to enable long-term sustainability of top-level HF care.

Diverging phenological responses of Arctic seabirds to an earlier spring - Sébastien Descamps; Francisco Ramírez; Sigurd Benjaminsen; Tycho Anker‐Nilssen; Robert T. Barrett; Zofia Burr; Signe Christensen‐Dalsgaard; Kjell‐Einar Erikstad; David B. Irons; Svein‐Håkon Lorentsen; Mark L. Mallory; Gregory J. Robertson; et al. (Global Change Biology, 2019)
The timing of annual events such as reproduction is a critical component of how free‐living organisms respond to ongoing climate change. This may be especially true in the Arctic, which is disproportionally impacted by climate warming. Here, we show that Arctic seabirds responded to climate change by moving the start of their reproduction earlier, coincident with an advancing onset of spring and that their response is phylogenetically and spatially structured. The phylogenetic signal is likely driven by seabird foraging behavior. Surface‐feeding species advanced their reproduction in the last 35 years while diving species showed remarkably stable breeding timing. The earlier reproduction for Arctic surface‐feeding birds was significant in the Pacific only, where spring advancement was most pronounced. In both the Atlantic and Pacific, seabirds with a long breeding season showed a greater response to the advancement of spring than seabirds with a short breeding season. Our results emphasize that spatial variation, phylogeny, and life history are important considerations in seabird phenological response to climate change and highlight the key role played by the species’ foraging behavior.

CHIPS: an Extensible Toolbox for Cellular and Hemodynamic Two-Photon Image Analysis - Matthew J. P. Barrett; Kim David Ferrari; Jillian L. Stobart; Martin Holub; Bruno Weber (Neuroinformatics, 2018)

CAR T Cells for Solid Tumors - Babak Moghimi; David Barrett (Current Stem Cell Reports, 2017)

Circumpolar dynamics of a marine top‐predator track ocean warming rates - Sébastien Descamps; Tycho Anker‐Nilssen; Robert T. Barrett; David B. Irons; Flemming Merkel; Gregory J. Robertson; Nigel G. Yoccoz; Mark L. Mallory; William A. Montevecchi; David Boertmann; Yuri Artukhin; Signe Christensen‐Dalsgaard; et al. (Global Change Biology, 2017)
Global warming is a nonlinear process, and temperature may increase in a stepwise manner. Periods of abrupt warming can trigger persistent changes in the state of ecosystems, also called regime shifts. The responses of organisms to abrupt warming and associated regime shifts can be unlike responses to periods of slow or moderate change. Understanding of nonlinearity in the biological responses to climate warming is needed to assess the consequences of ongoing climate change. Here, we demonstrate that the population dynamics of a long‐lived, wide‐ranging marine predator are associated with changes in the rate of ocean warming. Data from 556 colonies of black‐legged kittiwakes Rissa tridactyla distributed throughout its breeding range revealed that an abrupt warming of sea‐surface temperature in the 1990s coincided with steep kittiwake population decline. Periods of moderate warming in sea temperatures did not seem to affect kittiwake dynamics. The rapid warming observed in the 1990s may have driven large‐scale, circumpolar marine ecosystem shifts that strongly affected kittiwakes through bottom‐up effects. Our study sheds light on the nonlinear response of a circumpolar seabird to large‐scale changes in oceanographic conditions and indicates that marine top predators may be more sensitive to the rate of ocean warming rather than to warming itself.

The redistribution of non-breeding dunlins in response to the post-DDT recovery of falcons - Ronald C. Ydenberg; Jennifer Barrett; David B. Lank; Cailin Xu; Michiel Faber (Oecologia, 2017)

Population and Conservation Genetics in an Endangered Lemur, Indri indri, Across Three Forest Reserves in Madagascar - Schyler O. Nunziata; Peter Wallenhorst; Meredith A. Barrett; Randall E. Junge; Anne D. Yoder; David W. Weisrock (International Journal of Primatology, 2016)

Influence of Three Citrus Herbicides on Potential Production of Sorghum bicolor ‘Topper 76-6’ as a Bioenergy Crop - Patrick C. Wilson; Barrett Gruber; Youjian Lin; Prem Kumar; David Niebch; Sandra Wilson (Bulletin of Environmental Contamination and Toxicology, 2016)

Acute high-intensity interval rowing increases thrombin generation in healthy men - Matthew J. Sedgwick; Matthew Thompson; Jack Garnham; Alice E. Thackray; Laura A. Barrett; Matthew Powis; David J. Stensel (European Journal of Applied Physiology, 2016)

Species discovery and validation in a cryptic radiation of endangered primates: coalescent‐based species delimitation in M adagascar's mouse lemurs - Scott Hotaling; Mary E. Foley; Nicolette M. Lawrence; Jose Bocanegra; Marina B. Blanco; Rodin Rasoloarison; Peter M. Kappeler; Meredith A. Barrett; Anne D. Yoder; David W. Weisrock (Molecular Ecology, 2016)
Implementation of the coalescent model in a Bayesian framework is an emerging strength in genetically based species delimitation studies. By providing an objective measure of species diagnosis, these methods represent a quantitative enhancement to the analysis of multilocus data, and complement more traditional methods based on phenotypic and ecological characteristics. Recognized as two species 20 years ago, mouse lemurs (genus Microcebus ) now comprise more than 20 species, largely diagnosed from mt DNA sequence data. With each new species description, enthusiasm has been tempered with scientific scepticism. Here, we present a statistically justified and unbiased Bayesian approach towards mouse lemur species delimitation. We perform validation tests using multilocus sequence data and two methodologies: (i) reverse‐jump Markov chain Monte Carlo sampling to assess the likelihood of different models defined a priori by a guide tree, and (ii) a Bayes factor delimitation test that compares different species‐tree models without a guide tree. We assess the sensitivity of these methods using randomized individual assignments, which has been used in bpp studies, but not with Bayes factor delimitation tests. Our results validate previously diagnosed taxa, as well as new species hypotheses, resulting in support for three new mouse lemur species. As the challenge of multiple researchers using differing criteria to describe diversity is not unique to Microcebus , the methods used here have significant potential for clarifying diversity in other taxonomic groups. We echo previous studies in advocating that multiple lines of evidence, including use of the coalescent model, should be trusted to delimit new species.

Cystic echinococcosis in Southern Israel - Shalom Ben-Shimol; Orli Sagi; Ohad Houri; Elina Bazarsky; Anat Berkowitz; Shlomi Bulkowstein; Chiya Barrett; David Greenberg (Acta Parasitologica, 2016)
The aim of this retrospective, population-based study was to characterize demographically and clinically cystic-echinococcosis (CE) in southern Israel, between 2005 and 2012. Newly-diagnosed (nd-CE) and past-diagnosed (pd-CE, diagnosed before the study) cases were defined. Two populations live in southern-Israel, receiving medical treatment at a single hospital: the Jewish and the Bedouin populations (resembling resource-rich and resource-poor populations, respectively). 126 CE cases were identified; 55 nd-CE and 71 pd-CE. Mean annual nd-CE incidence per 100,000 in the Bedouin and Jewish populations were 2.7 ± 1.2 and 0.4 ± 0.3, respectively (P

Contrasting population trends at seabirds colonies: is food limitation a factor in Norway? - Emeline Pettex; Robert T. Barrett; Svein-Håkon Lorentsen; Francesco Bonadonna; Lorien Pichegru; Jean-Baptiste Pons; David Grémillet (Journal of Ornithology, 2015)

Dramatic increase in laboratory-diagnosed human cutaneous leishmaniasis cases in southern Israel, 2007–2013 - Shalom Ben-Shimol; Orli Sagi; Shlomi Codish; Victor Novack; Chiya Barrett; Yariv Fruchtman; Anat Berkowitz; Yonat Shemer-Avni; David Greenberg (Infectious Diseases, 2015)

Peptide Amphiphile Micelles Self-Adjuvant Group A Streptococcal Vaccination - Amanda Trent; Bret D. Ulery; Matthew J. Black; John C. Barrett; Simon Liang; Yulia Kostenko; Natalie A. David; Matthew V. Tirrell (The AAPS Journal, 2015)

A Report from the Pediatric Formulations Task Force: Perspectives on the State of Child-Friendly Oral Dosage Forms - Anne Zajicek; Michael J. Fossler; Jeffrey S. Barrett; Jeffrey H. Worthington; Robert Ternik; Georgia Charkoftaki; Susan Lum; Jörg Breitkreutz; Mike Baltezor; Panos Macheras; Mansoor Khan; Shreeram Agharkar; et al. (The AAPS Journal, 2013)

Telomere length and dynamics predict mortality in a wild longitudinal study - Emma L. B. Barrett; Terry A. Burke; Martijn Hammers; Jan Komdeur; David S. Richardson (Molecular Ecology, 2013)
Explaining variation in life expectancy between individuals of the same age is fundamental to our understanding of population ecology and life history evolution. Variation in the length and rate of loss of the protective telomere chromosome caps has been linked to cellular lifespan. Yet, the extent to which telomere length and dynamics predict organismal lifespan in nature is still contentious. Using longitudinal samples taken from a closed population of Acrocephalus sechellensis (Seychelles warblers) studied for over 20 years, we describe the first study into life‐long adult telomere dynamics (1–17 years) and their relationship to mortality under natural conditions ( n = 204 individuals). We show that telomeres shorten with increasing age and body mass, and that shorter telomeres and greater rates of telomere shortening predicted future mortality. Our results provide the first clear and unambiguous evidence of a relationship between telomere length and mortality in the wild, and substantiate the prediction that telomere length and shortening rate can act as an indicator of biological age further to chronological age when exploring life history questions in natural conditions.

“Modeling the impact of natural resource-based poverty traps on food security in Kenya: The Crops, Livestock and Soils in Smallholder Economic Systems (CLASSES) model” - Emma C. Stephens; Charles F. Nicholson; Douglas R. Brown; David Parsons; Christopher B. Barrett; Johannes Lehmann; David Mbugua; Solomon Ngoze; Alice N. Pell; Susan J. Riha (Food Security, 2012)

Multi-scale foraging variability in Northern gannet (Morus bassanus) fuels potential foraging plasticity - Emeline Pettex; Svein-Håkon Lorentsen; David Grémillet; Olivier Gimenez; Robert T. Barrett; Jean-Baptiste Pons; Céline Bohec; Francesco Bonadonna (Marine Biology, 2012)

Cranial biomechanics of Diplodocus (Dinosauria, Sauropoda): testing hypotheses of feeding behaviour in an extinct megaherbivore - Mark T. Young; Emily J. Rayfield; Casey M. Holliday; Lawrence M. Witmer; David J. Button; Paul Upchurch; Paul M. Barrett (The Science of Nature, 2012)

Disassortative mating and the maintenance of sexual polymorphism in painted maple - DAVID L. FIELD; SPENCER C. H. BARRETT (Molecular Ecology, 2012)
Since Darwin’s pioneering research on plant reproductive biology (e.g. Darwin 1877 ), understanding the mechanisms maintaining the diverse sexual strategies of plants has remained an important challenge for evolutionary biologists. In some species, populations are sexually polymorphic and contain two or more mating morphs (sex phenotypes). Differences in morphology or phenology among the morphs influence patterns of non‐random mating. In these populations, negative frequency‐dependent selection arising from disassortative (intermorph) mating is usually required for the evolutionary maintenance of sexual polymorphism, but few studies have demonstrated the required patterns of non‐random mating. In the current issue of Molecular Ecology , Shang et al. (2012) make an important contribution to our understanding of how disassortative mating influences sex phenotype ratios in Acer pictum subsp. mono (painted maple), a heterodichogamous, deciduous tree of eastern China. They monitored sex expression in 97 adults and used paternity analysis of open‐pollinated seed to examine disassortative mating among three sex phenotypes. Using a deterministic ‘pollen transfer’ model, Shang et al. present convincing evidence that differences in the degree of disassortative mating in progeny arrays of the sex phenotypes can explain their uneven frequencies in the adult population. This study provides a useful example of how the deployment of genetic markers, demographic monitoring and modelling can be integrated to investigate the maintenance of sexual diversity in plants.

A preliminary assessment of changes in plant-dwelling insects when threatened plants are translocated - Melinda L. Moir; Peter A. Vesk; Karl E. C. Brennan; Lesley Hughes; David A. Keith; Michael A. McCarthy; David J. Coates; Sarah Barrett (Journal of Insect Conservation, 2012)

Structural changes in the hippocampus and amygdala at first episode of psychosis - David R. Watson; Feng Bai; Suzanne L. Barrett; Aidan Turkington; Teresa M. Rushe; Ciaran C. Mulholland; Stephen J. Cooper (Brain Imaging and Behavior, 2012)

Platinum–palladium–gold mineralization in the Nkenja mafic–ultramafic body, Ubendian metamorphic belt, Tanzania - David M. Evans; Finn M. Barrett; Hazel M. Prichard; Peter C. Fisher (Mineralium Deposita, 2012)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Investigation of Design Space for Freeze-Drying: Use of Modeling for Primary Drying Segment of a Freeze-Drying Cycle - Venkat Rao Koganti; Evgenyi Y. Shalaev; Mark R. Berry; Thomas Osterberg; Maickel Youssef; David N. Hiebert; Frank A. Kanka; Martin Nolan; Rosemary Barrett; Gioval Scalzo; Gillian Fitzpatrick; Niall Fitzgibbon; et al. (AAPS PharmSciTech, 2011)

Formulation Development and In Vivo Evaluation of a New Dry Powder Formulation of Albuterol Sulphate in Beagle Dogs - Philip J. Kuehl; Edward G. Barrett; Jacob D. McDonald; Karin Rudolph; David Vodak; Dan Dobry; David Lyon (Pharmaceutical Research, 2010)

Stability in temperate reef communities over a decadal time scale despite concurrent ocean warming - RICK D. STUART‐SMITH; NEVILLE S. BARRETT; DAVID G. STEVENSON; GRAHAM J. EDGAR (Global Change Biology, 2010)
Despite increasing scientific and public concerns on the potential impacts of global ocean warming on marine biodiversity, very few empirical data on community‐level responses to rising water temperatures are available other than for coral reefs. This study describes changes in temperate subtidal reef communities over decadal and regional scales in a location that has undergone considerable warming in recent decades and is forecast to be a ‘hotspot’ for future warming. Plant and animal communities at 136 rocky reef sites around Tasmania (south‐east Australia) were censused between 1992 and 1995, and again in 2006 and 2007. Despite evidence of major ecological changes before the period of study, reef communities appeared to remain relatively stable over the past decade. Multivariate analyses and univariate metrics of biotic communities revealed few changes with time, although some species‐level responses could be interpreted as symptomatic of ocean warming. These included fishes detected in Tasmania only in recent surveys and several species with warmer water affinities that appeared to extend their distributions further south. The most statistically significant changes observed in species abundances, however, were not related to their biogeographical affinities. The majority of species with changing abundance possessed lower to mid‐range abundances rather than being common, raising questions for biodiversity monitoring and management. We suggest that our study encompassed a relatively stable period following more abrupt change, and that community responses to ocean warming may follow nonlinear, step‐like trajectories.

Species distributions, surrogacy, and important conservation regions in Canada - Leanna D. Warman; David M. Forsyth; A. R. E. Sinclair; Kathryn Freemark; Harold D. Moore; Thomas W. Barrett; R. L. Pressey; Denis White (Ecology Letters, 2004)
Conservation actions could be more efficient if there is congruence among taxa in the distribution of species. Patterns in the geographical distribution of five taxa were used to identify nationally important regions for conservation in Canada. Two measures of surrogacy were significantly and positively correlated among taxa, and conservation areas selected for one taxon represented other taxa significantly better than random selections. However, few large protected areas exist in the sites of highest conservation value in southern Canada; these regions are therefore a priority for future conservation regard. By focusing this effort on threatened and endangered species, which are a national priority in Canada, most other species could also benefit.

Effect of pollination and exogenous ethylene on accumulation of ETR1 homologue transcripts during flower petal abscission in geranium (Pelargonium × hortorum L.H. Bailey) - Christopher Dervinis; David G. Clark; James E. Barrett; Terril A. Nell (Plant Molecular Biology, 2000)

Nitrate in drinking water and the incidence of gastric, esophageal, and brain cancer in Yorkshire, England - Jennifer H. Barrett; Roger C. Parslow; Patricia A. McKinney; Graham R. Law; David Forman (Cancer Causes & Control, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Scale-up of Adhesive Transdermal Drug Delivery Systems - Glenn A. Van Buskirk; Mario A. González; Vinod P. Shah; Scott Barnhardt; Colin Barrett; Stephen Berge; Gary Cleary; Keith Chan; Gordon Flynn; Thomas Foster; Robert Gale; Raymond Garrison; et al. (Pharmaceutical Research, 1997)

Polychlorinated biphenyls and organochlorine pesticides in milk and blood of Canadian women during lactation - Jos Mes; John A. Doyle; Barrett R. Adams; David J. Davies; Davida Turton (Archives of Environmental Contamination and Toxicology, 1984)